Young Women Leaders Program (YWLP) Longitudinal Follow-up Study, Central Virginia, 2013-2015 - Deutsch, Nancy L. ([Verlag nicht ermittelbar], 2020)
Although delinquency among adolescent girls is rising, little research exists on the long-term effects of prevention programs meant for them. This project is a long-term evaluation of a gender-specific program, the Young Women Leaders Program (YWLP), a one-on-one and group-based mentoring program, in preventing delinquency and related outcomes in girls at-risk for delinquency. The primary research questions included: 1) Is YWLP effective long-term in preventing or reducing delinquency and associated risk outcomes in at-risk adolescent girls? 2) What do mentees and mentors identify as key mentoring and relationship processes related to effective mentoring? 3) Do key mentoring and relationship processes moderate the effects of the mentoring intervention in preventing or reducing girls' delinquency and associated risk outcomes during high school? Researchers collected five-year follow-up surveys from girls who participated in an evaluation of YWLP from 2007-2010. The sample includes two cohorts of girls (2008-09 and 2009-10) who were randomly assigned to participate in YWLP or in a control group during their seventh grade year, as well as a third cohort (2007-2008) of non-randomized program and control girls used to pilot test recruitment strategies and measures, and to boost the sample size for analyses. In the original study, girls were nominated at the end of sixth grade because of individual or demographic characteristics related to delinquency risk and were assigned to YWLP or a control group condition; they completed one pre- and two post-assessments during seventh grade. The research team followed up with the girls five years later and administered surveys focused on key academic, social, emotional, and behavioral indicators. A secondary goal is to assess the role of mentoring processes and relationship quality in explaining girls' long-term outcomes. The research team interviewed a subset of girls and their mentors who were identified as having the highest and lowest quality mentoring relationships during the program (based on their scores on a relational quality scale from the original study). The interview data explores what girls and mentors remember about their mentoring relationships five years later, how they think the program affected them, if at all, and what aspects of the relationships they recalled as helping or hindering the relationship. Data in this release contain two parts: DS1--survey data and DS2--interview transcripts.